PENGEMBANGAN LKPD BERBASIS MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS - Kiki Herdiansyah (Eksponen, 2018)
This research aimed to analyze student worksheet development based on Problem Based Learning model in topic of Probability for Senior High School students of grade X. The instruments which were used in this research were the validation sheet of student worksheet for math lecturer and teacher in order to fulfill the validity aspect, the student scoring sheet in order to fulfill the applicability aspect, and critical mathematic thinking ability test in order to fulfill the effectiveness aspect. The result of the research showed that the student worksheet which was based on Problem Based Learning model had fulfilled the requirements and appropriateness standard based on content, design, and language expert. The data analysis of t-test towards of critical thinking ability showed that the critical thinking ability of students with Problem Based Learning model worksheet was higher than the critical thinking ability of students without Problem Based Learning model worksheet.